Building brand loyalty and brand lovemark through celebrity endorsement: A Sub Saharan Africa perspective : Marka Bağlılığı ve Aşk Markası Oluşturmada Ünlü Kullanımı: Sahara Altı Afrika’da Bir Araştırma - Bah, Mohamed Sheriff (My University, 2018)
Bu çalışmada temel olarak tüketicilerin algısının incelenmesine odaklanılmaktadır. Bu kapsamda, bir markanın iletişim faaliyetlerinde ünlü kullanmasının markanın imajına, bilinirliğine ve bunun sonucunda marka sevgisine ve sadakatine etkisi Sahra-altı Afrika’da incelenmiştir. Aynı zamanda iletişim faaliyetlerinde kullanılan ünlülerin hangi özelliklerinin belirtilen değişkenler üzerinde nasıl bir etkisinin bulunduğu da araştırmanın odak noktasını oluşturmaktadır.Çalışmanın giriş bölümü konuyla ilgili tanımlara genel bir bakış sunmaktadır. İkinci bölüm, ünlü kullanımı hakkındaki mevcut literatürü gözden geçirmekte ve araştırma konusunun önemini daha fazla açıklığa kavuşturan içgörüler sunmaktadır.Üçüncü bölüm, metodoloji bölümüdür. Bu bölümde niteliksel ve niceliksel yöntemler kullanılarak yapılan araştırma bulguları ve araştırma metodolojisi özetlenmiştir.Dördüncü bölüm, bulguları göstermek için kullanılan grafik çizimler aracılığı ile veri analizlerine ve bulgulara odaklanmıştır. Veriler, bir anket yoluyla toplanmıi ve daha sonra basit ama etkili bir Microsoft olan SPSS istatistik paketleri gibi veri analiz Excel elektronik tablosu kullanılarak analiz eedilmiştir. Tezin son bölümü, tüm araştırma sonuçlarını özetlemiş ve ünlü kullanımı yaklaşımını geliştirmeye yardımcı olabilecek önerileri sunmuştur.iiiÇalışmada Afrika'daki tüketici algılarının, iletişim faaliyetlerinde ünlü kullanımının marka sevgisi ve marka sadakati üzerinde büyük bir etkisi olabileceğini ve bu etkinin marka bilinirliğini ve marka imajını artırabileceği sonucuna ulaşmıştır. Bulgulara dayanarak, tüketicilerin ünlülerin kullanımının ünlü olmayanlara kıyasla daha çekici ve etkili olarak değerlendirdiği sonucuna varmıştır. Dahası, genellikle ünlü kullanımının marka aşkı, marka bilinirliği ve marka sadakatini etkilediği bulgusuna ulaşılmıştır.

The utilization of celebrity endorsement has become popular in recent times. Celebrities have become pervasive elements in the marketing industries, especially in Sub-Saharan Africa, thereby improving the brand image, brand loyalty, and brand love for businesses in diverse sectors of emerging economies. Thus, celebrity endorsement, in itself, has become one of the most profitable businesses across the globe and has had a significant influence on marketing. Marketers involve celebrities in their marketing strategies to influence buyers’ brand perception and also influence the overall sales revenue and product market share. This paper majorly focuses on the examination of the perception of consumers: A Sub-Sahara African perspective in regards to celebrity endorsement and how this approach influences an organization’s brand image, brand loyalty, and brand love. Also, which attributes of celebrities affect these brand dimensions are also examined in the study.The introductory chapter of the paper gives an overview of celebrity endorsement, and definitions. The second chapter reviews the existing literature on celebrity endorsement and provides insights into the research, which gives more clarification on the importance related to the topic. The third chapter is the methodology section and utilizes both qualitative, in terms of the many electronic discussions, some interviews and the body of literature reviewed, and quantitative method that utilizes analytic surveys and random sampling to investigate the perception of consumers on celebrity endorsement and the impact it has on advertising strategy on brand building. The fourth chapter focuses on data analysis andvfindings whereby graphical illustrations are used to indicate the findings. The data is collected through a questionnaire and later analyzed using data analysis software programs like the SPSS statistical packages and Excel spreadsheet, a basic but effective Microsoft programme to analyse data. The final chapter of the thesis concludes the entire research and provides the recommendations that can help improve the approach of celebrity endorsement.The study assumes that consumer perceptions in Africa shows that celebrity endorsement may have huge effect on brand love and brand loyalty and that impact could increase brand awareness and brand image. Based on the findings, it concludes that consumers actually consider celebrity endorsements more attractive and influential as compared to non-celebrity endorsements. It further discovers that generally celebrity endorsement does impact brand love, brand awareness and brand loyalty.
Keywords: Advertising Strategy; Brand Image; Brand Love; Brand Loyalty; Brand name products; Branding (Marketing); Celebrity Endorsement; Consumer behavior; Management; Marka Sadakati Marka Aşkı Consumers; Markalaşma (Pazarlama); Markalı ürünler; Marketers; Marketing; Müşteri ilişkileri; Pazarlama; Pazarlamacılar; Reklam Stratejisi Marka Imajı; Tüketici; Tüketici davranışı; Ünlü Ciro; Yönetim